DİFERANSİYEL OPERATÖRLERİN SPEKTRAL TEORİSİNDE AÇILIM TEOREMLERİ - ALGÜN, AKIN (Fırat Üniveristesi, 2017)
Bu çalışma dört bölümden oluşmaktadır. Birinci bölümde tez içerisinde kullanacağımız temel tanım ve teoremlere yer verilmiş aynı zamanda Sturm-Liouville operatörünün bazı temel özellikleri incelenmiştir. İkinci bölümde Sturm-Liouville operatörü için Osilasyon Teorisi incelenmiş. Birinci ve ikinci mukayese teoremi ile Sturm osilasyon teoremi ve genel osilasyon teoremi incelenmiştir. Üçüncü bölümde integral denklemler ve sonlu farklar metodu ile açılım teoremlerinin ispatı yapılmıştır. Dördüncü bölümde Fourier-Bessel açılımı incelenmiştir.

This thesis consists of four chapters. In the first chapter, some concepts which are used in this thesis are given and some fundamental properties of Sturm Liouville operator are examined. In the second chapter, the Sturm-Liouville operator for Oscillation Theory has been investigated. The first and second comparison theorems and Sturm Oscillation theorem and General oscillation theorem have been investigated. In the third chapter, Integral equations and finite difference method and expansion theorem have been mentioned and the expansion theorem's evidence has been taken. In the fourth chapter, Fourier-Bessel expansion examined.
Spectral theory of differential operators opening theorems
Keywords: Matematik